2023
DOI: 10.1029/2022jd037738
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Aerosol Effect on Liquid Cloud Microphysical Properties in the Warm Season Over Tibetan Plateau

Abstract: The effect of aerosol on liquid cloud microphysical properties over the Tibetan Plateau (TP) during the warm season is investigated by using aerosol index (AI) and cloud property parameters data. Distinct differences in aerosol effect on liquid cloud microphysical properties have been found between the northern Tibetan Plateau (NTP) and southernTibetan Plateau (STP). The composite liquid cloud droplet effective radius liquid cloud droplet effective radius (LREF) anomalies for positive AI events are positive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…There are differences in ACIs among different cloud phases. Due to the less complex microphysical processes in liquid-phase clouds, which do not involve mixed-phase and ice-phase processes, there have been many research findings on the interaction between aerosols and liquid-phase clouds [9,12,[19][20][21][22][23][24][25][26][27][28]. Numerous studies have found a negative correlation between cloud droplet size and aerosol concentration in liquid-phase clouds, consistent with the traditional aerosol indirect effect or "Twomey effect" by using satellites, aircraft, ground-based observations, etc.…”
Section: Introductionmentioning
confidence: 69%
“…There are differences in ACIs among different cloud phases. Due to the less complex microphysical processes in liquid-phase clouds, which do not involve mixed-phase and ice-phase processes, there have been many research findings on the interaction between aerosols and liquid-phase clouds [9,12,[19][20][21][22][23][24][25][26][27][28]. Numerous studies have found a negative correlation between cloud droplet size and aerosol concentration in liquid-phase clouds, consistent with the traditional aerosol indirect effect or "Twomey effect" by using satellites, aircraft, ground-based observations, etc.…”
Section: Introductionmentioning
confidence: 69%
“…Previous studies have also found that dust aerosols dominate the aerosol composition in the WTP (Duo et Liu et al 2015). In WTP, the warm season is higher in water vapor content than the cold season, which is more conducive to the activation of dust aerosols with larger particle sizes to form cloud droplets and promotes the increase of the effective radius of cloud droplets (Zhao et al 2023). In IGP, during the warm season, positive correlations are observed between AOD anomaly and both LREF anomaly and IREF anomaly.…”
Section: Figures 6a and 6b Show The Correlation Between Aod Anomaly A...mentioning
confidence: 94%
“…Under stable atmospheric conditions, aerosol leads to the activation of cloud droplets through vapor consumption. The droplets then continue to grow through condensation (Zhao et al 2023). The growth of cloud droplets may further promote the development of cloud macrophysical properties.…”
Section: Constraints Of Meteorological Conditions On the Aerosol-clou...mentioning
confidence: 99%
See 1 more Smart Citation
“…The direct radiative forcing effects of light absorbing aerosols are very important on the TP and consequently affect the Asian monsoon (Kumar et al., 2011; Lau et al., 2006; Qian et al., 2011). Atmospheric aerosols also affect cloud formation and consequently affect cloud albedo and hydrological cycles on the TP (Jin, 2006; Zhao et al., 2023; Zhao, Xiao, et al., 2022). The TP has glacier and snow cover, and atmospheric aerosols such as black carbon can accelerate the melting of snow and ice (Lee et al., 2017; Li et al., 2018; Sharma et al., 2022) and affect hydrological cycles via deposition (Yao et al., 2012).…”
Section: Introductionmentioning
confidence: 99%